Fatigue properties of self‐piercing riveted multi‐rivet joints in steel and aluminum sheets. Issue 12 (17th December 2019) - Du, G.; Xing, Y.; Li, X.
Abstract: Self‐piercing riveting (SPR) is an important joining technology for connecting steel and aluminum sheets. In this paper, AA6111 aluminum alloy and DP780 high‐strength steel were adopted to study the influence of fatigue on remaining static strength and energy absorption properties on self‐piercing riveting multi‐rivet joints. The results showed that energy absorption capacity of the specimens decreased significantly after high cycle fatigue. Fatigue reduced the remaining static lap shear strength of riveted specimens. Scanning electron microscopy (SEM) was used to analyze the cross section of fatigue specimens fractured by static tension. The results showed that fretting wear was found at the contact area between rivet and aluminum sheets. Fatigue bands and fatigue cracks appeared in fatigue specimens after high cycle fatigue, while those with low cycle fatigue specimens did not appear. Small cracks weaken the strength of the aluminum sheet, resulting in the static tensile strength of the riveted specimen with high cycle fatigue is lower than that of other fatigue specimens.